De Noordelyckste Zee Kusten van America van Groenland door de Straet Davis ende Straet Hudson tot Terra Neuf = Septemtrionaliora Americae à Groenlandia per Freta Davidis et Hudson, ad Terram Novam. Title (alt.): Septemtrionaliora Americae à Groenlandia per Freta Davidis et Hudson, ad Terram Novam - Wit, Frederik de (1675)
Map of the northern coast of Acadia and the western coast of Greenland. Appears in the author's Atlas [Zeekaerten]. Tot Amsterdam: bij Frederick de Wit, 1675? Color; 1:2,218,000